THE EFFECT OF THE PROPORTION OF SORGUM FLOUR (Sorghum bicolor) AND JACKFRUIT SEED FLOUR (Artocarpus heterophyllus) ON THE PHYSICOCHEMICAL AND ORGANOLEPTIC PROPERTIES OF CRISPY GLUTEN FREE BROWNIES - Angelie Lavionda; Bambang Sigit Sucahyo; Retnani Rahmiati; Yuda Agustian (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Crispy brownies are a popular bakery product innovation due to their crispy texture and distinctive taste. With the increasing interest in gluten-free foods, the use of local non-wheat raw materials such as sorghum flour (Sorghum bicolor) and jackfruit seed flour (Artocarpus heterophyllus) is important to develop as an alternative to wheat flour. Both ingredients have the potential to support the physicochemical and organoleptic quality of the product. This study aims to examine the effect of variations in the proportion of the two flours and determine the optimal formulation of gluten-free crispy brownies . The study used an experimental method with a completely randomized design (CRD) with one factor , namely the difference in the concentration of the combination of sorghum flour and jackfruit seed flour. The treatment consisted of 5 levels, namely P1 (90 %: 10%), P2 (80%: 20%), P3 (70%: 30%), P4 (60%: 40%), and P5 (50%: 50%), each treatment was repeated 3 times. The parameters tested included water content, protein content, breaking strength test, and organoleptic tests (color, aroma, taste , texture). Data were analyzed using parametric statistics through Analysis of Variance (ANOVA) with the help of SPSS 24 software. If there were significant differences between treatments, the analysis was continued using the Tuckey test . Organoleptic data with the hedonic test method based on the panelists' level of preference were tested with Kruskal Wallis. The results showed that variations in the proportion of the two flours did not have a significant effect ($p>0.05$) on all parameters tested, including water content, protein content, breaking strength, and organoleptic attributes (color, aroma, taste, and texture). All treatments had organoleptic characteristics in the "Neutral" category with an average score ranging from 3.44 to 3.98. Based on the effectiveness test, treatment P1 (90% sorghum flour: 10% jackfruit seed flour) was determined as the best formulation with the highest Yield Value (NH) of 0.738, which had a water content of 2.41%, a protein content of 7.38%, a breaking strength of 441.73 gf, and organoleptic scores of color 3.86, taste 3.84, aroma 3.78, and texture 3.98.